The influence of housing types and price on abandon housing projects in Malaysia - Saidah An'nisaa, Salam; Nur Farhayu, Ariffin; Mohamad Idris, Ali; Noram Irwan, Ramli; Nor Hasanah, Abdul Shukor Lim (Construction Research Institute of Malaysia, 2019)
Housing construction is one of the most important economic activities in Malaysia and taken seriously by the government. However, the housing project in Malaysia still faces the abandoned issue due to several problems. Abandoned housing projects happen across the globe, and is an issue that gives negative effects to the stakeholders of those projects. This study was conducted to study one of the factors which is the influence of housing types and price on housing abandonment in Malaysia, specifically in Peninsular Malaysia. This paper also reviewed the other factors that contribute to this matter such as improper market study, mismanagement, financial problem, land and legal disputes, lack of project risk assessment, inapplicable government policy, incompetent workers, lack of enforcement and inconsistent monitoring by the authorities. Together, the economic analysis was presented to analyse the impact of housing project abandonment to the economy of the country. This paper will contribute to the body of knowledge in terms of abandoned buildings in Malaysia.